2020
DOI: 10.1002/advs.202003263
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Profile Evaluates Response and Survival to First‐Line Chemotherapy in Lung Cancer

Abstract: Evaluating the therapeutic response and survival of lung cancer patients receiving first‐line chemotherapy has always been difficult. Limited biomarkers for evaluation exist and as a result histology represents an empiric tool to guide therapeutic decision making. In this study, molecular signatures associated with response and long‐term survival of lung cancer patients receiving first‐line chemotherapy are discovered. Whole‐exome sequencing is performed on pretherapeutic tissue samples of 186 patients [145 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…After that, samples from 122 qualifying advanced lung cancer patients were eligible, including 86 NSCLC and 36 SCLC participants ( Table S1 ). Tumor specimens and blood samples were collected as we previously described ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, samples from 122 qualifying advanced lung cancer patients were eligible, including 86 NSCLC and 36 SCLC participants ( Table S1 ). Tumor specimens and blood samples were collected as we previously described ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Tissue DNA or RNA was extracted based on the manufacturer’s protocol, and reversed transcript would be performed for extracted RNA for subsequent PCR amplification. EGFR mutations and EML4-ALK fusion were detected as described ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…For DNA extraction and quantification, we used QIAamp DNA Tissue Kit (Qiagen, Valencia, USA), RelaxGene Blood DNA system (Tiangen, Beijing, China), Fluorometer (Qubit 2.0), and the Qubit dsDNA HS assay kit (Thermo Fisher Scientific, CA, USA). Once we obtained fragmented genomic DNA by particular instrument and reagents ( 28 , 29 ), we constructed DNA library by Kapa Biossystems (MA, USA). Then, fragments with poor quality were excluded, while remaining reads were amplified by a certain circulation of polymerase chain reaction.…”
Section: Methodsmentioning
confidence: 99%
“…With the help of Genome Analysis ToolKit (V 4.1) and Mutect2, DNA fragments were aligned to hg19 reference genome (GRch37), thus detecting somatic mutation, single nucleotide variants, and insertion-deletion mutations. Eventually, according to conventional formula for TMB calculation ( 28 ), the somatic TMB value of each case was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…The therapeutic response and survival of lung cancer patients without EGFR or anaplastic lymphoma kinase (ALK) driver gene alterations receiving first-line chemotherapy are difficult to predict. Recently, He et al [9] showed that molecular signatures could only provide limited information. In this study, NSCLC patients were classified into four subtypes based on genomic alteration characteristics, however, no survival difference between the subtypes were observed.…”
mentioning
confidence: 99%